Technology and the right to strike: conflicting realities - Maria Carmen Aguilar Del Castillo (Labour & Law Issues, 2018)
Article 28.2 of the Spanish Constitution recognises the right to strike to defend workers’ interests. As the positive regulation of this right is contained in a pre-constitutional provision dated 1977, its configuration as a fundamental right comes from interpretation and constitutional case law. The application of the Royal Decree 1977 to technology-based actions of the employer has led the Constitutional Court to deny the violation of the right to strike, and therefore to consider technological strike-breaking as a guarantee for workers' rights. Including the simple absence from work in the right to strike and excluding the ability to limit employer’s power, is a restrictive interpretation of the essential content of the right. According to this, we consider the technological strike-breaking as an abusive conduct of the employer detrimental to the right to strike. The Constitutional Court does not take into account its previous rulings. It states that, without express prohibition, there is no technological strike-breaking if the employer, during a strike, uses the material resources at his disposal to avoid the harmful consequences of collective abstention, as such conduct expresses freedom of enterprise. The Court does not take into account the primacy of the right to strike on the freedom of enterprise and not only because of its position in the constitutional text, but also because the interpretation of a fundamental right cannot imply a denial of the right itself.